2010
DOI: 10.1177/156482651003100304
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Quality Protein Maize in Improving the Nutritional Status of Young Children in the Ethiopian Highlands

Abstract: Background. Undernutrition is a persistent problem in Africa, especially

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 22 publications
3
69
0
1
Order By: Relevance
“…Bio-fortified crops bred for improved nutritional quality can alleviate nutritional deficiencies if they are produced and consumed in sufficient quantities [35]. Several studies in controlled settings have indicated the positive impact of QPM on the nutritional status of human consumption and animal feeds [12,34,[36][37][38][39][40][41].…”
Section: Nutritional Quality and Impact Of Qpmmentioning
confidence: 99%
“…Bio-fortified crops bred for improved nutritional quality can alleviate nutritional deficiencies if they are produced and consumed in sufficient quantities [35]. Several studies in controlled settings have indicated the positive impact of QPM on the nutritional status of human consumption and animal feeds [12,34,[36][37][38][39][40][41].…”
Section: Nutritional Quality and Impact Of Qpmmentioning
confidence: 99%
“…Using meta-analysis and community-based approach, Gunratna et al (2010) studied the nutritional impact of QPM, which revealed that consumption of QPM instead of conventional maize led to a 12% increase in the rate of growth in weight and a 9% increase in the rate of growth in height in infants and young children with mild-to-moderate undernutrition from populations, with maize as staple food. In another study on young children in the Ethiopian highlands, the inclusion of QPM in children's diet could reduce or prevent growth faltering and may in some cases support catch-up growth in weight (Akalu et al 2010). Clearly, more such studies are needed to assess the efficacy of biofortified crops on human health.…”
Section: Efficacy Of Biofortified Crops On Human Healthmentioning
confidence: 99%
“…Diverse QPM genotypes adapted to sub-Saharan Africa have now been developed (Hohls et al 1996;CIMMYT 2005;Krivanek et al 2007; Badu-Apraku and Lum 2010; Musila et al 2010) and their nutritional benefits for children have been documented (Akalu et al 2010). Two approaches have been used to develop QPM germplasm adapted to ESA.…”
Section: Introductionmentioning
confidence: 99%